Prices of Agricultural Products and Poverty: How Strongly are the Two Linked? - Muhammad Arsyad (Hasanuddin University, 2019)
Prices of agricultural products and poverty relationship are the two types of standing issue to solve. This paper tries to argue that price of agricultural products (hereafter, agricultural price) and poverty are strongly related. We employed Correlation (intermediate step) and Path (final step) in the analysis procedure. The results show that, first, the association degree between agricultural input (note as well, that price is crucial factor to get input) with poverty approaching 70%, indicating that agricultural input is good-fit in explaining poverty. Second, the higher the frequency of getting agricultural extension, and price information for various inputs (and output) in agriculture, the higher the crop productions (agricultural sector, in broad sense) will be gained. This indicates these two variables (inputs-outputs prices) can also be expected to be important instruments in increasing smallholders’ income and in turn help them living above poverty line. Farmers household income is strongly affected by prevailing market price. Agricultural price is functioning as intermediate part of income calculation. It is clear that price of agricultural products has a strong linkage with rural poverty alleviation in the country.